PENGGUNAAN PONSEL PINTAR DENGAN HOT POTATOES-JCLOZE UNTUK PEMBELAJARAN MENYIMAK BAHASA JEPANG - Luza Qodriyanti (Universitas Negeri Surabaya, 2019)
This paper aims to explain the steps of making Japanese language media that can be used in smart phones with listening material using the Hot Potatoes device and to find out the difficulties and obstacles that occur in its application in the classroom. The media products produced with Hot Potatoes are in the form of HTML file formats that can be opened in almost any smartphone browser. The Hot Potatoes media products are made in such a way that students can listen and interact with the media. This study used descriptive qualitative method. The study was conducted on 58 students of SMAN 1 Probolinggo as media users. From the results of the questionnaire, observations and interviews, it is known that Hot Potatoes media works well in almost all smartphone browsers. The obstacle is that when the process of distributing files takes a long time, the voice player feature does not work. After further observation, these problems can be overcome so students are ready to use the Hot Potatoes-JCloze media for listening learning with all its limitations.